POP UP RETAIL ACCEPTANCE BY THE CUSTOMERS IN MANADO (CASE STUDY: MOFFEE COFFEE STORE) - Noertamin, Excellent; Saerang, David P.E.; Tumewu, Ferdinand J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Pop-up retail through its experiential marketing is currently developing; it has been used as one of marketing strategy not only for known company but also for start-up businesses in Manado. Pop-up retail such as pop-up cafés is implementing experiential marketing as their new way of marketing strategy to increase profit, recognized and to reach out their market. Word of Mouth which is the product of experiential marketing becomes a powerful weapon for pop-up cafés. The researcher conducted this research to investigate whether pop-up retail is effective marketing strategy toward customers in Manado and is it accepted or not. This study uses qualitative method with exploratory approach. Meanwhile in-depth interview is used to collect the data among the respondents which are Moffee Coffee Store customers. Findings of this research show that pop-up retail concepts as marketing strategy influence Moffee Coffee Store customers in many aspects significantly such as customer?s loyalty and brand recognition. From the results, Moffee Coffee Store as a pop-up café as their marketing strategy is accepted by customers in Manado. It is recommended that a pop-up retail to be more customer-oriented as the way how pop-up retail should be to give a memorable experience to the customers. Keywords: pop-up retail, experiential marketing, word of mouth